The Relationship between Gentle Tactile Stimulation on the Fetus and Its Temperament 3 Months after Birth - Zhe-Wei Wang; Jing Hua; Yu-Hong Xu (Behavioural Neurology)
Objective. The aim of this study was to evaluate the effect of gentle tactile stimulation on the fetus in its temperament 3 months after birth. Method. A total of 302 mother-3-month-infant dyads enrolled the retrospective cohort study. 76 mothers had regular gentle tactile stimulation on the fetus in their pregnancy; 62 mothers had irregular tactile stimulation on the fetus, and the rest of 164 mothers who had no tactile stimulation served as nonexposure group. Temperament was assessed using the EITS (a nine-dimensional scale of temperament). Results. Significant difference in temperament type was found among infants in 3 groups at 3 months of age. In the regular practice group, the babies with easy type temperament accounted for 73.7%, which was higher than that in irregular practice group (53.2%, P=0.012) and that in the control group (42.1%, P<0.001). Compared to infants in no practice group, the infants who had received regular gentle tactile stimulation before birth were lower in negative mood (P=0.047) while higher in adaptability (P<0.001), approach (P=0.001), and persistence (P=0.001), respectively. Conclusion. Regular gentle tactile stimulation on fetus may promote the formation of easy type infant temperament.